BUILDING THE YOUNG LEARNERS ENGLISH VOCABULARY BY USING THE SMART CARD AT MBS SANG SURYA - Hidayati Hidayati; Rima Rahmaniah; M. Hudri (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2019)
Abstract: Smart card  as a medium of teaching language is regarded as central elements of the approach because it can be used as media to attract the young learners interest in learning language especially English language. The writer try to adopt this media in the classroom, especially by using a smart card to make  the  lesson  more easier and  interesting for the young learners to build their vocabulary in english. In relation, the purpose of this research is to investigate does the use of smart card has effect in building vocabulary in english to MBS DayCare learners. The researcher applied true exprimental research design as the methodology with 20 young learners as the population and all of them taken as a sample by using rubric and t-test formula theory according Hughes. The researcher collect the data by using testing method. The result of this research showed that mean score of experimental group 8 and mean score of control group 7. Based on t-test, it showed that t- value 3,782 and after cosulting to t-table, the t-value was higher than t-table. The smart card in vocabulary learning process is more effective to enrich the learners’ vocabulary, this can be seen from the results of test score that the experimental class which was given treatment using smart card media got higher score than control class without taught by used smart card  media. The writer concluded that smart card has an effect in building vocabulary in english at Daycare learners in Muhammadiyah Boarding School (MBS) Sang Surya. Abstrak: Tujuan dari penelitian ini adalah untuk menyelidiki apakah penggunaan kartu pintar berpengaruh dalam membangun kosa kata dalam bahasa Inggris untuk pelajar MBS DayCare. Peneliti menerapkan desain penelitian exprimental sejati sebagai metodologi dengan populasi 20 siswa sebagai populasi dan semuanya diambil sebagai sampel dengan menggunakan teori rumus rubrik dan uji-t menurut Hughes. Peneliti mengumpulkan data dengan menggunakan metode test. Hasil penelitian ini menunjukkan bahwa skor rata-rata kelompok eksperimen adalah 8 dan skor rata-rata kelompok kontrol adalah 7. Berdasarkan uji-t, menunjukkan bahwa nilai t-hitung sebesar 3,782 dan setelah korelasikan dengan t-tabel, t-hitung lebih tinggi daripada t-tabel. Kartu pintar dalam proses pembelajaran kosakata lebih efektif untuk memperkaya kosakata peserta didik, hal ini dapat dilihat dari hasil skor tes bahwa kelas eksperimen yang diberi perlakuan menggunakan media kartu pintar mendapat skor lebih tinggi daripada kelas kontrol tanpa diajar dengan menggunakan media kartu pintar. Penulis menyimpulkan bahwa kartu pintar berpengaruh dalam membangun kosa kata dalam bahasa Inggris.